Grading of agarwood oil quality based on its chemical compounds using self organizing map (SOM) - Mohamad Hushnie, Haron; Mohd Nasir, Taib; Nurlaila, Ismail; Nor Azah, Mohd Ali; Saiful Nizam, Tajuddin (The World Academy of Research in Science and Engineering, 2020)
Agarwood oil is derived from resin saturated heartwood of Agarwood tree using solvent extraction, hydro-distillation and etc. The oil consists ofcomplex mixtures of chromone derivatives, oxygenated sesquiterpenes and sesquiterpene hydrocarbonsand they are significant in determining the quality of Agarwood oil. In this paper, a study focusing on the determination of high and low grades of Agarwood oil quality using SOMwas carried out. Three chemical compounds namely β-agarofuran, α-agarofuran and 10-epi-φ-eudesmol were used as inputs for SOM. In addition, KNN was used to confirm the Agarwood oil grades. This technique wasthen validated using independent samples. The results show that SOM was able to determine the high and low gradesof Agarwood oil with average silhouette indexes between reasonable and excellent, and KNN was able to confirmthese grades with 100% accuracies. In conclusion, the Agarwood oil quality gradingtechnique based on SOM was successfulin determining the Agarwood oil quality into high and low.